(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The production, purification, as well as improvement of biogas as a clean and renewable fuel substitute has gotten a lot of attention. Biogas is produced by anaerobic digestion and includes methane, carbon dioxide, as well as trace amounts of many other gases. Biogas purification removes trace gases from the biogas, making it safe to use. Biogas upgrading produces methane-rich biogas by removing excessive carbon dioxide from the gas mixture. A number of carbon dioxide extraction technologies may be utilized for biogas upgrading. Chemical carbon dioxide absorption for biogas upgrading, on either hand, is crucial since it functions at or near ambient temperature as well as pressure, reducing energy consumption. This article discusses the chemical absorption of carbon dioxide via amine scrubbing, caustic liquid scrubbing, and amino acid saline water swabbing. Each of these biogas-upgrading methods is described. The study suggests that further research is needed to optimize the use of chemical absorption methods for biogas upgrading.